Microplasmedha Comic: A Supplementary Learning Resource on Environmental Pollution Material to Improve High School Students’ Knowledge of Microplastics - Choirin Nashiroh; Shefa Dwijayanti Ramadani; Ika Sukmawati (FKIP - Universitas Riau, 2026)
The global plastic waste problem has led to the formation of microplastics, which negatively affect the environment and human health. Therefore, education about microplastics is important for high school students to increase environmental awareness and promote sustainable behavior. Although many studies have explored microplastics and related educational approaches, research on the development of comics as a learning media for microplastic education remains limited. This study aimed to develop the Mikroplasmedha comic as a supplementary learning resource on environmental pollution and assess the effectiveness of the comic in supporting student learning. The study employed a Research and Development (R&D) method using the ADDIE model, consisting of the Analysis, Design, Development, Implementation, and Evaluation stages. The results showed that the Mikroplasmedha comic obtained validation scores of 84.1% and 73.3% from media and subject matter experts, respectively, indicating that it was categorized as very valid and valid. Furthermore, the effectiveness test yielded an N-gain score of 0.52, indicating a moderate improvement in students' knowledge of microplastics after reading the comic. In addition the practicality aspect, assessed through student response questionnaires, also showed an average score of 81.9%, which falls into the good category. These findings indicate that the Mikroplasmedha comic is valid and moderately effective as a supplementary learning resource for improving secondary school students' knowledge of microplastics.